DEVELOPMENT OF INFORMATION SYSTEM STRATEGIES AND INFORMATION TECHNOLOGY AT PRIVATE UNIVERSITIES IN PRINGSEWU BY USING METHODOLOGY ENTERPRISE ARCHITECTURE PLANNING (EAP) - Ahmad Khumaidi; Eka Ridhawati (Bakti Nusantara Institute, 2017)
The development of information systems and information technology requires planning to complement the direction of the college strategy. Planning is constructed by defining data, application and technology architectures in the use of information to support business processes and then architectural design to identify needs and create architectural schemes and make plans for their implementation. Enterprise Architecture Planning (EAP) is a method of data quality planning approach oriented to business needs and how the implementation of the architecture is done in such a way in an effort to support business turnover and achievement of Vision and Mission and the goal of strategic development of SI and IT at college private high. The result of this research is to get the blueprint resulting from Enterprise Architecture Planning (EAP) methodology which will be used as a guide for making blueprint in the form of data architecture, application architecture and technology architecture in strategy development Information system and information technology as a whole on High private sector especially in Pringsewu